2020
DOI: 10.3390/math8101829
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Design and Implementation of a Quadrotor Unmanned Aerial Vehicle Using Quaternion-Based Estimator

Abstract: The main goal of the research is to design a low-cost, performing quadrotor unmaned aerial vehicle (UAV) system. Because of low cost limits, the performance must be ensured by other ways. The present proposal is a quaternion-based estimator used in the control loop. In order to make the proposed solution easy to be reproduced by the reader, step-by-step instructions are given, including component choices, design, and implementation. Throughout the article, detailed description of the system model is given. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Therefore, if there is no feedback control, the quadrotor UAV system is unstable. In order to make the unstable system stable, it is necessary to design corresponding controllers to achieve good control effect 12 . The following figure 2 shows the feedback control system of the quadrotor UAV.…”
Section: Control System Design Of Quadrotor Uavmentioning
confidence: 99%
“…Therefore, if there is no feedback control, the quadrotor UAV system is unstable. In order to make the unstable system stable, it is necessary to design corresponding controllers to achieve good control effect 12 . The following figure 2 shows the feedback control system of the quadrotor UAV.…”
Section: Control System Design Of Quadrotor Uavmentioning
confidence: 99%
“…Hence, there exists a limit to be used for compact UAVs. For low-cost devices in measurement and control, a research suggested an accurate and economical method of estimating information on drone sensors [ 23 ]. As suggested in [ 23 ], if an advanced controller replaces the classical PID controller, a quadrotor with outstanding performance can be presented.…”
Section: Introductionmentioning
confidence: 99%
“…For low-cost devices in measurement and control, a research suggested an accurate and economical method of estimating information on drone sensors [ 23 ]. As suggested in [ 23 ], if an advanced controller replaces the classical PID controller, a quadrotor with outstanding performance can be presented. In this study, we designed an SMC that enables quickly tracking and stabilizing the quadcopter.…”
Section: Introductionmentioning
confidence: 99%